Lacrosse Player's Sprint Ability: The Relationship Between 30M Cradle Sprint and Medicine Ball Throw - Yuya Maruo (CV. FOUNDAE, 2025)
Background: Few studies have examined the sprinting capacity of female lacrosse players compared to other field-based sports. Sprinting ability in lacrosse, particularly when players are cradling the ball, may differ from traditional sprinting, as handling the ball can affect acceleration and overall speed.Aims: This study aimed to investigate the relationship between sprinting ability and medicine ball throws in female collegiate lacrosse players. Specifically, it sought to compare sprint performance with and without cradling and examine how medicine ball throw performance correlates with sprinting ability.Methods: Twenty-two participants (19.9 ± 1.2 years) were recruited from a collegiate lacrosse team. They performed 30m and cradle sprint trials from a standing start. Additionally, participants conducted medicine ball throws with 1kg, 2kg, and 3kg weights. Sprint times were recorded for 0-10m and a total of 30m distances.Results: The time for the total 30m distance was significantly shorter in the regular 30m sprint trial than in the 30m cradle trial. The 0-10m segment was slower in the cradle sprint trial than the regular sprint trial. Faster individuals in the 30m sprint trial were associated with longer distances in the 1kg and 2kg medicine ball throws. In comparison, faster individuals in the 30m cradle sprint trial were correlated with longer distances in the 1kg, 2kg, and 3kg medicine ball throws.Conclusion: The cradle affects acceleration from a stopped position. Additionally, sprinting ability while cradling the ball is correlated with performance in the 3kg medicine ball throw, suggesting a relationship between upper-body strength and sprint performance in lacrosse.